Integrating communities into tourism planning through social innovation - Malek, Anahita (2015)
This study proposes a framework that provides a new combined effective strategy for implementation of community participation into tourism planning as a social innovation phenomenon. The underlying idea is creation of innovative and appropriate development strategies to involve local communities as a key agent in the decision-making and planning of tourism destinations in order to ensure positive local attitudes and improvement in communities’ quality of life. Utilizing the information gathered from the (ECoC), Guimarães 2012, as the case study, this paper discusses a complex concept that encapsulates the main dimensions of the community tourism development and social innovation in practice. Community-based development initiatives of the city of Guimarães included in the development programme for the ECoC 2012 are evaluated in the context of governance structure, networking and direct participation of local communities. Results not only indicate operational constrains in governance arrangements and flaws in community participation strategies, but also suggest the need for collaborative initiatives and the need for application of a system perspective that includes all elements of sustainable community involvement.